2023
DOI: 10.1002/jcp.30988
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid exosomes regulate OVGP1 secretion in yak oviduct epithelial cells via autophagy in vitro

Abstract: After mammalian ovulation, oocytes enter the oviduct, causing oocyte and oviduct changes. Some studies have shown that follicular fluid exosomes (FEVs) play an important role in this regulatory process, but the specific mechanism is remains unclear. Here, we investigate the effect of FEVs on autophagy and on the synthesis and secretion of oviductal glycoprotein 1 (OVGP1) in yak oviduct epithelial cells (OECs). We added FEVs to yak OECs and collected samples at intervals. The effect of autophagy on OVGP1 synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The PI3K/AKT signaling pathway, known for its role in insulin signaling, is closely associated with adipogenesis [ 32 ]. Although previous studies on yaks have primarily focused on fibroblast proliferation [ 33 ], intestinal inflammation [ 34 ], and reproduction [ 35 ], there is limited research on fat metabolism. Numerous studies have indicated that miR-129 is involved in regulating the PI3K/AKT pathway [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway, known for its role in insulin signaling, is closely associated with adipogenesis [ 32 ]. Although previous studies on yaks have primarily focused on fibroblast proliferation [ 33 ], intestinal inflammation [ 34 ], and reproduction [ 35 ], there is limited research on fat metabolism. Numerous studies have indicated that miR-129 is involved in regulating the PI3K/AKT pathway [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the cells related to the yak that have been isolated and cultured include yak germ cells, precursor adipocytes, rumen epithelial cells, fetal fibroblasts, mammary epithelial cells, etc. [ 9 , 10 , 11 , 12 ]. It is of great significance to construct an important yak population cell line to conserve its genetic resources from the perspective of our germplasm resource conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Its fertility could hardly meet the demands of herdsmen and restrict the increase in yak population, as a result of relatively late sexual maturity and short estrous period of 1-2 days even in lush pasture. At present, there have been studies on the uterus (Abudureyimu et al, 2018), oviduct (Wang et al, 2023), lung (Ge et al, 2021), and heart (He et al, 2016) of yaks, but in the transition between luteal phase and follicular phase of yaks, important regulatory proteins in the cycle transition still need to be explored.…”
mentioning
confidence: 99%